Graphics design works: service / Hana Khaleeda Suhardi - Suhardi, Hana Khaleeda (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2024)
Swee Kang is a dessert establishment that has been serving customers since 1953. It is known for its shaved ice desserts, and it is one of the best dessert shops in Kuching, Sarawak. Swee Kang is undergoing a rebranding process to incorporate a vintage theme to attract global tourists. These include a commercial video and booth, with a vintage-themed Chinese cultural logo.